Study Pengembangan Pendidikan dan Pelatihan bagi Aparatur Sipil Negara Berbasis Implementasi Model Addie - Ketut Rusmulyani (Universitas Indraprasta PGRI Jakarta, 2020)
Development of Education and Training for State Civil Apparatuses requires a simple, easy to use, and certainly systematic stage. One development model that can be used is the Addie model. The purpose of this study is to determine the stages of development of Education and Training for State Civil Apparatuses using the Addie model and to determine the implication of the Addie model in Education and Training for State Civil Apparatus. This research is library research. The Addie model applied in this study was able to identify the development of Education and Training for State Civil Apparatuses in depth. The results of this study also showed that the quality of the training that had taken place so far had been good. Thus, the development of training needs to be continued. But the form of development needs to be studied scientifically so that its development products can be a solution in solving training problems.